2021
DOI: 10.3390/ijms22136657
|View full text |Cite
|
Sign up to set email alerts
|

Chr15q25 Genetic Variant rs16969968 Alters Cell Differentiation in Respiratory Epithelia

Abstract: The gene cluster region, CHRNA3/CHRNA5/CHRNB4, encoding for nicotinic acetylcholine receptor (nAChR) subunits, contains several genetic variants linked to nicotine addiction and brain disorders. The CHRNA5 single-nucleotide polymorphism (SNP) rs16969968 is strongly associated with nicotine dependence and lung diseases. Using immunostaining studies on tissue sections and air-liquid interface airway epithelial cell cultures, in situ hybridisation, transcriptomic and cytokines detection, we analysed rs16969968 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…nAChR is a nicotine‐dependent receptor, and its expression level plays an important role in the development of smoking‐related diseases, especially respiratory diseases, 9 such as chronic obstructive pulmonary disease (COPD) and lung cancer. Genome‐wide association studies have shown that CHRNA5 gene (encoding α5‐nAChRs [α5‐nAChR]) polymorphisms are significantly related to the occurrence and development of cancer, especially lung cancer 10,11 ; it is highly expressed in esophageal cancer, gastric cancer and lung cancer and plays an important role in tumor cell proliferation, invasion and metastasis 12 . Our previous studies have shown that α5‐nAChR mediates the development and progression of nicotine‐induced lung cancer, activates Hif‐1α/VEGF, JAK2/STAT3, and Jab/Csn5 signaling, and promotes the proliferation and migration of lung cancer cells 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…nAChR is a nicotine‐dependent receptor, and its expression level plays an important role in the development of smoking‐related diseases, especially respiratory diseases, 9 such as chronic obstructive pulmonary disease (COPD) and lung cancer. Genome‐wide association studies have shown that CHRNA5 gene (encoding α5‐nAChRs [α5‐nAChR]) polymorphisms are significantly related to the occurrence and development of cancer, especially lung cancer 10,11 ; it is highly expressed in esophageal cancer, gastric cancer and lung cancer and plays an important role in tumor cell proliferation, invasion and metastasis 12 . Our previous studies have shown that α5‐nAChR mediates the development and progression of nicotine‐induced lung cancer, activates Hif‐1α/VEGF, JAK2/STAT3, and Jab/Csn5 signaling, and promotes the proliferation and migration of lung cancer cells 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…The eight papers published in this SI described case studies that may provide a useful framework for understanding the general molecular defects underlying a broad and diverse spectrum of human diseases. These included multifactorial or polygenic disorders, such as lung cancer (OMIM*612052) and osteoporosis (OMIM*166710) [ 1 , 2 ], or monogenic disorders, such as Long QT Syndrome 1 (LQT; OMIM*192500), Hyaline fibromatosis syndrome (OMIM*228600), Dystrophic epidermolysis bullosa (RDEB; OMIM*226600), Xeroderma Pigmentosum C Phenotype (XP-C; OMIM*278720), and MTHFR deficiency (OMIM*236250) [ 3 , 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%
“…Two of the SI-published works investigated the role of novel genetic variants in the ANTXR2 and LRP5 genes identified by NGS of affected individuals from selected cohorts [ 2 , 4 ]. Diabasana et al studied the molecular effects of a small nucleotide polymorphism (SNP) of CHRNA5 gene, known to confer susceptibility for lung disease [ 1 ]. Beilin et al investigated the correlation between specific mutations, selected among hundreds of COL7A1 reported variants, and the varying severity of cutaneous manifestation [ 5 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations